Light-activated gas sensing: a perspective of integration with micro-LEDs and plasmonic nanoparticles. Issue 3 (4th January 2021) - Suh, Jun Min; Eom, Tae Hoon; Cho, Sung Hwan; Kim, Taehoon; Jang, Ho Won
Abstract : Light-activated gas sensors have been investigated for their superior potential to replace current thermally activated gas sensors. This review summarizes the various efforts made for their development and provides an overview of the progress. Abstract : Light-activated gas sensors have been investigated for their superior potential to replace current thermally activated gas sensors, which have several drawbacks for the Internet of Everything application. This review summarizes the various efforts made for the development of light-activated gas sensors and provides an overview of their progress. The light-activated gas sensing properties of metal oxides, 2D materials, and other candidate materials are summarized. As strategies to overcome the current challenges of light-activated gas sensors, the effects of nanostructures and crystallographic orientations are discussed. Finally, the incorporation of plasmonic nanoparticles and integration with micro light-emitting diodes are proposed for the pathway toward the real application of light-activated gas sensors. This review should offer a broad range of readers a new perspective toward the future development of light-activated gas sensors.